Molecular characterization of hepatitis A virus isolated from acute infections in Turkey - Bedia Dinç; Duygu KOYUNCU; Senem Ceren Karataylı; Elife BERK; Ersin Karataylı; Mehmet PARLAK; İnci ÇELİK and Miray AKGÜÇ and Rüçhan SERTÖZ and Mustafa BERKTAŞ and et al. (Turkish Journal of Gastroenterology, 2019)
-